2003
DOI: 10.1258/00222150360600878
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural ciliary changes of maxillary sinus mucosa following functional endoscopic sinus surgery: an image analysis quantitative study

Abstract: This was a study of the effect of functional endoscopic sinus surgery (FESS) on the ciliary regeneration of maxillary sinus mucosa in patients with chronic maxillary sinusitis, using objective quantitative methods. Twenty specimens from the mucosa of both the superolateral wall and the ostium of the maxillary sinus were sampled during FESS and then six to 12 months later. They were light examined first by light microscopy and then by scanning electron microscopy in combination with image analysis software in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…Although the ciliary area may return to normal after FESS, [7,17] ciliary dysmorphology and abnormality of secretory elements may persist, causing ongoing impairment of MCC, potentially contributing to sinusitis relapse [19]. In the present study, ciliary knobs and an increased number of submucosal glands were noted for both mucosal types post FESS, although patients were free of symptoms and the maxillary mucosa were grossly normal.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Although the ciliary area may return to normal after FESS, [7,17] ciliary dysmorphology and abnormality of secretory elements may persist, causing ongoing impairment of MCC, potentially contributing to sinusitis relapse [19]. In the present study, ciliary knobs and an increased number of submucosal glands were noted for both mucosal types post FESS, although patients were free of symptoms and the maxillary mucosa were grossly normal.…”
Section: Discussionmentioning
confidence: 51%
“…Bassiouny et al [17], found that the CA of the superolateral maxillary sinus wall decreased to 10.12% in adult patients with chronic paranasal sinusitis before operation and then increased to 50.72%, 8.1 months after FESS. In contrast, Guo et al [7] reported that the CA of the superolateral maxillary sinus wall dropped to 60.7% before operation and increased to 74.3% in adult patients with chronic sinusitis, 7 months after FESS.…”
Section: Discussionmentioning
confidence: 97%
“…The normal physiological activity of the regenerated cilia still needs further study [3]. However, the assessment by saccharin test indirectly corrobarates that the ciliary function is near normal / normal following FESS.…”
Section: Discussionmentioning
confidence: 98%
“…Articles related to the above observation was not reported in the literature so far. The ciliary area is calculated using scanning electron microscopy by studying the surface of relatively large areas of mucosa using software image analysis [3]. In our study a manual gross observatory analysis is done because of lack of software image analysis programme.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts to studies on the distribution of cilia in nasal mucosa which are more common in the literature and are based on more accurate recent techniques such as image analysis computer systems. [6][7][8] Shimada and Lim in 1972 studied the distribution of ciliated cells in the normal human middle-ear mucosa and showed that the distribution and density of ciliated epithelial cells decreased in an anterior to posterior direction from over 80 per cent of the total mucosal surface in the eustachian tube, to 11-50 per cent in the remainder of the promontory, to one to 10 per cent in the prominence of the facial canal and to less than one per cent in the mastoid cavity. 1 In cases of chronic suppurative otitis media (CSOM) some authors have shown that the cilia of the mucous membrane undergo structural and quantitative changes 9,10 while others did not reach this conclusion.…”
Section: Introductionmentioning
confidence: 99%